PERTIMBANGAN HAKIM DALAM MENJATUHKAN PUTUSAN PIDANA BERDASARKAN HASIL SIDANG LAPANGAN (Descente) PADA TINDAK PIDANA KORUPSI (Analisis Putusan Nomor : 15/Pid.Sus-TPK/2019/Pn Jmbi dan Putusan Nomor 60/Pid.Sus-TPK/2017/PN.Mdn.) - Sriyono, Dudy (Universitas Ekasakti, 2021)
Field trials or local examinations (descente), there is no normative regulation in the Criminal Procedure Code. Field hearings or local inquiries (descente) are regulated normatively in civil procedural law in Article 153 HIR (Herzeine Inlandsch Reglement). Field hearings (descente) in court proceedings in cases of corruption in the procurement of government goods and services, In case Number 15 / Pid.Sus-TPK / 2019 / Pn Jambi, a field trial was conducted at the location of the object of the case, namely the Tanduk River D.I Irrigation Network, located in Sungai Tanduk Village, Kayu Aro District. Based on the results of the field review by the Panel of Judges, it was evident that the D.I Sungai Tanduk irrigation network was functioning well. The results of the field trial in the judge's decision were used as a consideration for the mitigating circumstances for the defendant. In Decision Number 60 / Pid.Sus-TPK / 2017 / PN.Mdn. a field trial was held in which the Public Prosecutor presented the Auditor and the Legal Counsel for the Defendant to present the Auditor and from the results of the field trial, it was found that state financial losses amounted to IDR 75,522,786.10 (seventy-five million five thousand twenty-two seven hundred eighty-six rupiah ten cents). The judgment of the high court judges regarding the results of the field trials conducted was that the audit results were updated, independent, accepted by both parties and real facts on the ground (real) so that they were used in the verdict. Second, the Power of Evidence Against the Implementation of Field Sessions from these two decisions, it can be seen that field examinations have the same evidentiary power as a trial conducted in a courtroom, namely binding on the judge in making a decision.